THE LEADERSHIP ROLE OF MADRASAH HEADS IN IMPROVING TEACHER PERFORMANCE THROUGH HUMAN RESOURCE MANAGEMENT IN PRIVATE MADRASAS - Alfin Muttaqin Rambe; Sumitro; Hayanuddin (SOSIOEDUKASI, 2026)
This study aims to analyze the leadership role of madrasah heads in improving teacher performance through Islamic value-based human resource management (HRDM) at MTs Al-Ikhlas Kebun Ajamu. The research uses a qualitative approach with a descriptive design. Data was collected through in-depth interviews, observations, and documentation, and analyzed using an interactive model that included data reduction, data presentation, and conclusion drawing with validity test through triangulation. The results of the study show that the leadership of madrasah heads is participatory and transformational, which is able to encourage teacher motivation, involvement, and professionalism. The implementation of MSDM is carried out systematically through planning, recruitment, coaching, and performance evaluation by integrating Islamic values such as trust, responsibility, and discipline in the work culture. The synergy between leadership and HRM based on Islamic values has been proven to improve teacher performance, which is shown by improvements in learning planning, more innovative learning implementation, more systematic evaluation, and improved professional development. This research offers an integrative model between leadership, human resources, and Islamic values as a contribution to the development of madrasah education management.